2010
DOI: 10.2495/dn100381
|View full text |Cite
|
Sign up to set email alerts
|

New attitude in polymers – self-healing

Abstract: Elastomeric polymers are nowadays used in a broad variety of highly demanding applications. Due to alternating loads, microsized cracks may occur in the material, even before its loading-and lifetime-limit. The consequences can be drastic -failure of components often leads to the loss of production, delays, raising costs or facilities and -in rarely cases -personal injuries. Our endeavour is the equipment of such technically relevant elastomers with a self-healing agent. If microcracks occur in the material, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Over the last thirty years, considerable research has led to the development of polymer systems that heal in various ways: activated or autonomous, repeatable or not. [1][2][3][4][5][6][7][8][9][10] In particular, healable rubbers [11][12][13][14] and gels, [15][16][17] which can both heal and sustain large elastic deformations are of great interest for many applications like adhesives, 18 coatings [19][20][21] or implants and scaffolds for tissue engineering. 22,23 Recently, a novel type of rubber having a molecular architecture based on supramolecular chemistry 24 has been designed to exhibit a remarkable self-healing property.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last thirty years, considerable research has led to the development of polymer systems that heal in various ways: activated or autonomous, repeatable or not. [1][2][3][4][5][6][7][8][9][10] In particular, healable rubbers [11][12][13][14] and gels, [15][16][17] which can both heal and sustain large elastic deformations are of great interest for many applications like adhesives, 18 coatings [19][20][21] or implants and scaffolds for tissue engineering. 22,23 Recently, a novel type of rubber having a molecular architecture based on supramolecular chemistry 24 has been designed to exhibit a remarkable self-healing property.…”
Section: Introductionmentioning
confidence: 99%
“…After a full cut being made on the stretchable electrode, the two pieces were physically in contact with a good alignment. The electrode was able to recover high conductivity and 40% of stretchability after 3 days of self‐healing, which indicates the reconstruction of Au thin film due to the autonomous self‐repairing of SEBS [ 42,46–48 ] (Figure 4E, Figures S15d and S16, Supporting Information). To test the tearing damage endurance of DS memristor in a serious condition, a full cut along the diagonal of the crossbar is applied to a working cell of device.…”
Section: Resultsmentioning
confidence: 99%
“…Main chain flexibility accelerates the process by chain interdiffusion. In the case of ballistic damage, it was found that a high ionic content does not necessarily result in higher self-healing efficiency (Kalista et al, 2007;Nellesen et al, 2010).…”
Section: Chemical/physical Healing By Reversible Bondsmentioning
confidence: 99%